Menerapkan Strategi Pembelajaran Kelas Rangkap - Ahmad Secha Rahmadi; Alya Rifa Dwi Pangestu; Eva Nesalia; Rafa Lola Amanda; Riri Oktavia Erlina; Ufara Alfadila (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The implementation of multi-grade learning strategies is an alternative solution to overcome the limited number of teachers in remote areas. This strategy requires teachers to manage two or more grade levels in the same space and time. This study aims to analyze the effectiveness of implementing multi-grade learning strategies through an integrated thematic approach and the use of local-based learning media. The results show that teachers who use flexible lesson planning, heterogeneous grouping of students, and the use of active learning methods are able to increase student engagement and more equitable learning outcomes between grade levels.